Psychosocial Adjustment in Ugandan Children: Coping With Human Immunodeficiency Virus Exposure, Lifetime Adversity, and Importance of Social Support. Issue 171 (3rd July 2020) - Tuke, Robert; Sikorskii, Alla; Zalwango, Sarah K.; Webster, Kyle D.; Ismail, Alexander; Pobee, Ruth A.; Barkin, Jennifer L.; Boivin, Michael J.; Giordani, Bruno; Ezeamama, Amara E.
Abstract: Cumulative lifetime adversity and social support were investigated as determinants of psychosocial adjustment (esteem, distress, hopefulness, positive outlook/future aspirations, and sense of purpose) over 12 months in 6–10‐years‐old HIV‐infected, HIV‐exposed uninfected and HIV‐unexposed uninfected children from Uganda. Each determinant and psychosocial adjustment indicator was self‐reported using standardized questionnaires administered at baseline, 6, and 12 months. Linear mixed effects models were used to relate time‐varying lifetime adversity and social support to psychosocial adjustment over 12 months. Regardless of HIV status, higher adversity predicted lower esteem (coefficient b = −2.98, 95% confidence interval (CI): [−4.62, −1.35]) and increased distress ( b =3.96, 95% CI: [1.29, 6.62]) but was not associated with hopefulness, positive outlook or sense of purpose. Low social support predicted higher distress ( b =9.05, 95% CI: [7.36, 10.73]), lower positive outlook ( b = −10.56, 95% CI: [−2.34, −8.79]) and low sense of purpose ( b = −9.90, 95% CI: [−11.44, −8.36]) over 12 months. Pragmatic interventions that enhance coping with adversity and provide emotional/instrumental support should be tested for effectiveness in promoting resilient psychosocial adjustment trajectory in vulnerable children.